Forming of precision thin-wall hollow electron beams for microwave generators - Agafonov, A.V.; Krastelev, E.G.; Lebedev, A.N.; Voronin, V.S.; Lebedev, P.N. (Вопросы атомной науки и техники, 1999)
The electron gun producing the precision hollow relativistic electron beam for coherent microwave generator applications has been developed and tested. It is based on the large non-adiabatic compression of the beam emitted by ring-shaped cathode with an active surface big enough to produce a wanted current level. Further improvement of beam quality is possible by decreasing of the width of the annular emitter and increasing its emissive power.